Self-Identity Formation of Public Officials on Entertainment Apps : (Study on the Use of Tiktok) - Yanuar Galih Wiryawan (LONTAR: Jurnal Ilmu Komunikasi, 2022)
The TikTok application focuses on the age of 25-30 years with the demographics of Javanese people with middle to upper socioeconomic status groups. However, the use of the application is not only by youth and the general public; celebrities and public officials also use the application for their purposes. This research will focus on public officials' use of the TikTok application in forming self-identities. This study uses a constructive paradigm with a descriptive qualitative research method. The research design used in this study is phenomenological. The phenomenon raised in this study is to see the use of the TikTok application in building self-identity from the point of view of symbolic interaction theory. The results of the discussion found that there is a broad community role in displaying self-identity on TikTok. The community consists of a team, colleagues, family, and TikTok users. The interactions that occur form an identity that continues to develop from the research subject.